1957
DOI: 10.1017/s0022029900008578
|View full text |Cite
|
Sign up to set email alerts
|

658. Factors influencing the vitamin content of milk fat: IV. The source of milk fat vitamin A and carotene

Abstract: With 2 Figures)'During the course of investigations into factors affecting the vitamin content of New Zealand milk fats(i, 2,3) the need for further information about the source of the milk fat vitamin A and carotene became apparent. Experiments were therefore carried out to investigate the relationship between the levels of carotene and vitamin A ester in the blood plasma and milk fat, and to assess the relative contributions of vitamin A of hepatic origin (through the blood plasma vitamin A alcohol) and vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1957
1957
1981
1981

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For vitamin A secretion, however, the picture is complicated by the presence of both vitamin A alcohol and ester in the blood, and the above arguments presuppose esterification of vitamin A alcohol in the mammary gland. While plasma vitamin A ester may be the main source of milk fat ester (12), there seems ample evidence of the ability of the mammary gland to esterify plasma alcohol fairly completely (13). If esterification also occurs in the synthesis of colostrum, the process must be remarkably efficient, since very little vitamin A alcohol appears in colostral fat, the levels found in this investigation ranging from a maximum of l-6fig./g.…”
Section: Discussionmentioning
confidence: 63%
“…For vitamin A secretion, however, the picture is complicated by the presence of both vitamin A alcohol and ester in the blood, and the above arguments presuppose esterification of vitamin A alcohol in the mammary gland. While plasma vitamin A ester may be the main source of milk fat ester (12), there seems ample evidence of the ability of the mammary gland to esterify plasma alcohol fairly completely (13). If esterification also occurs in the synthesis of colostrum, the process must be remarkably efficient, since very little vitamin A alcohol appears in colostral fat, the levels found in this investigation ranging from a maximum of l-6fig./g.…”
Section: Discussionmentioning
confidence: 63%
“…The plasma vitamin A is taken up as the alcohol form but is secreted in the colostral fat mainly as the ester (Thompson & McGillivray, 1957). In experiments in which cows were transferred from pasture to a carotenefree diet, McGillivray (1957b) showed that there was no immediate change in levels of carotene in the plasma, yet the milk-fat carotene decreased from 7 -2 to 3.0 pglg in 7 days. It seems reasonable to suggest therefore, on analogy with plasma vitamin A alcohol and ester, that there may be two distinct forms of carotene in the blood plasma.…”
Section: Factors Injluencing the Vitamin A And Carotene Content Of Comentioning
confidence: 99%